2017
DOI: 10.3389/fmicb.2017.01554
|View full text |Cite
|
Sign up to set email alerts
|

Zika Virus: What Have We Learnt Since the Start of the Recent Epidemic?

Abstract: Zika is a viral disease transmitted mainly by mosquitoes of the genus Aedes. In recent years, it has expanded geographically, changing from an endemic mosquito-borne disease across equatorial Asia and Africa, to an epidemic disease causing large outbreaks in several areas of the world. With the recent Zika virus (ZIKV) outbreaks in the Americas, the disease has become a focus of attention of public health agencies and of the international research community, especially due to an association with neurological d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0
4

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 250 publications
(375 reference statements)
0
47
0
4
Order By: Relevance
“…Since the recent outbreak in 2015 in the Americas, a quite high number of possible antiviral candidates are being tested in vitro and in vivo. However, until now, no specific therapy has been approved against any flavivirus [18], including ZIKV [19] and, thus, current treatments are mainly directed to symptoms relief, such as fever and rash, by administering antipyretics, anti-histamines, and fluids for dehydration [15]. Nevertheless, it should be noted that some commonly used drugs, such as acetylsalicylic acid, are contraindicated in ZIKV-infected patients, since they increase the risk of internal bleeding, and other arboviruses (dengue or chikungunya viruses) that can co-infect the patients may produce hemorrhages [3].…”
Section: Therapeutic Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the recent outbreak in 2015 in the Americas, a quite high number of possible antiviral candidates are being tested in vitro and in vivo. However, until now, no specific therapy has been approved against any flavivirus [18], including ZIKV [19] and, thus, current treatments are mainly directed to symptoms relief, such as fever and rash, by administering antipyretics, anti-histamines, and fluids for dehydration [15]. Nevertheless, it should be noted that some commonly used drugs, such as acetylsalicylic acid, are contraindicated in ZIKV-infected patients, since they increase the risk of internal bleeding, and other arboviruses (dengue or chikungunya viruses) that can co-infect the patients may produce hemorrhages [3].…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…In males, ZIKV can infect testes, prostate and seminal vesicles [12,13] and in females it can infect vagina, uterus, vaginal epithelium, uterine fibroblasts, Hofbauer cells, trophoblasts, and endothelial cells from the placenta [12,14]. ZIKV has also been detected in the cornea, neurosensory retina, optic nerve, aqueous humor, and tears [15]. Because of this, ZIKV infection can lead to severe neurological and ophthalmological disorders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another potential source of study bias is underreporting, as shown by Romero-Vega et al ( 37 ) for dengue in Colombia; the National Health Institute of Colombia calculated an underreporting rate of 49% for Zika in a high-incidence town in Colombia ( 38 ). However, we used the same data that the Colombia authorities use to generate public health information for making decisions about controlling and preventing activities of public and private health institutions, extending the current information produced by the public health surveillance system, supporting surveillance activities for Zika and dengue, providing information for monitoring the geographic distribution of both diseases, and characterizing spatially the disease distribution in the population ( 39 ). …”
Section: Discussionmentioning
confidence: 99%
“…Unlike development processes, viral life cycles occur in a readily observable time frame that can be initiated, stopped, or modified by investigators. Finally, this work provides yet another example of viruses teaching us new cell biology with its insight into non-centrosomal micro-tubule regulation by EB proteins, not to mention a potential antiviral drug for a virus that causes over 8,000 birth defects in the US alone each year-four times more than the total worldwide caseload of congenital Zika syndrome (Britt, 2017;Permar et al, 2018;Saiz et al, 2017).…”
mentioning
confidence: 99%